Pengaruh Metode Mutqin Al-Muyassar Pada program Tahfidz dalam meningkatakn Hafalan Al-Qur’an Siswa di SDIT Mufidatul Ilmi - Ayu annur fani; Sujinal Arifin; Asri Karolina (STKIP Subang, 2025)
This study aims to determine the effect of the Mutqin Al-Muyassar method on improving students’ Qur’an memorization at SDIT Mufidatul Ilmi, Banyuasin Regency. The research used a quantitative approach with a One Group Pretest–Posttest Design. The subjects consisted of 30 fifth-grade students enrolled in the tahfidz (Qur’an memorization) program. Data were collected through memorization tests (pretest and posttest), classroom observations, and student questionnaires. The data were analyzed using a paired sample t-test to determine the significance of improvement in memorization performance after applying the Mutqin Al-Muyassar method. The results revealed a significant increase in students’ Qur’an memorization ability after using the Mutqin Al-Muyassar method. The average pretest score of 59.2 increased to 84.7 in the posttest, with a significance value (Sig. 2-tailed) of 0.000 < 0.05. This indicates that the Mutqin Al-Muyassar method effectively enhances students’ fluency, tajwid accuracy, and memorization retention. Moreover, 93% of students reported higher motivation and enjoyment in participating in the tahfidz sessions due to the engaging and structured nature of the method. Therefore, this method can be recommended as an effective learning strategy in Islamic elementary schools to foster a generation that loves and memorizes the Qur’an wholeheartedly.